2010
DOI: 10.1007/s12032-010-9749-z
|View full text |Cite
|
Sign up to set email alerts
|

Weekly regimen of epirubicin and paclitaxel as second-line chemotherapy in patients with metastatic transitional cell carcinoma of urothelial tract: results of a phase II study

Abstract: Until recently, there was no standard second-line treatment for advanced urothelial carcinoma. Although included in first-line regimens, role of anthracyclines was never investigated as second-line therapy. Single-agent paclitaxel showed modest results in this setting. The purpose of this study was to assess the efficacy and toxicity of concomitant weekly administration of epirubicin plus paclitaxel in patients with metastatic urothelial carcinoma previously treated with platinum-based regimens. Between March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
(39 reference statements)
0
3
1
Order By: Relevance
“…In our study, median OS and median TTP were slightly shorter than those reported by Rozzi et al [9] (12.6 and 7.6monthsvs.8.9and3.8months,respectively),butthelevels oftoxicityinourstudywerecomparable.Thelowersurvival rates in our study may be associated with higher rates of extranodal involvement and enrolment of patients with an ECOGperformancestatusof2.Inconclusion,inlightofthis retrospective study, 3-weekly paclitaxel plus doxorubicin could represent an interesting option in patients with urothelial carcinoma of the urinary tract, who have failed to respondtoplatinum-andgemcitabine-basedchemotherapy.…”
Section: Toxicitycontrasting
confidence: 77%
See 2 more Smart Citations
“…In our study, median OS and median TTP were slightly shorter than those reported by Rozzi et al [9] (12.6 and 7.6monthsvs.8.9and3.8months,respectively),butthelevels oftoxicityinourstudywerecomparable.Thelowersurvival rates in our study may be associated with higher rates of extranodal involvement and enrolment of patients with an ECOGperformancestatusof2.Inconclusion,inlightofthis retrospective study, 3-weekly paclitaxel plus doxorubicin could represent an interesting option in patients with urothelial carcinoma of the urinary tract, who have failed to respondtoplatinum-andgemcitabine-basedchemotherapy.…”
Section: Toxicitycontrasting
confidence: 77%
“…Toxicities in this study were of a mild and acceptabledegree,whileonly1patientsufferedfromfebrile neutropeniaandonly3patientshadgrade3peripheralneuro-pathy [9].…”
Section: Toxicitymentioning
confidence: 60%
See 1 more Smart Citation
“…These 10 trials were used to discover the potential role of selected new risk factors because they were already available and had been previously used for other retrospective analyses. Thereafter, 5 other phase II trials of salvage therapy were pooled in the validation dataset 1620 . All of these trials required previous pathological confirmation of UC and the presence of measurable metastatic disease.…”
Section: Methodsmentioning
confidence: 99%